A Phenotypic Analysis of Involucrin-Membrane-Bound Ovalbumin Mice after Adoptive Transfer of Ovalbumin-Specific CD8+ T Cells - Yujin Nakagawa; Gyohei Egawa; Toshiya Miyake; Saeko Nakajima; Atsushi Otsuka; Takashi Nomura; Akihiko Kitoh; Teruki Dainichi; Jun-ichi Sakabe; Akihiko Shibaki; Yoshiki Tokura; Tetsuya Honda; et al. (Elsevier, 2022)
To investigate the mechanism of autoimmunity and peripheral tolerance in the skin, several transgenic mouse strains expressing membrane-bound ovalbumin (mOVA) as an epidermal self-antigen under the control of keratinocyte-specific promotors, such as keratin 5 and keratin 14, were employed in combination with adoptive transfer of CD8+ T cells from OT-I mice (OT-I T cells) that recognize an ovalbumin-derived peptide. However, these strains showed bodyweight loss and required additional inflammatory stimuli, such as γ-irradiation and tape-stripping, to induce skin inflammation. In this study, we generated a mouse strain expressing mOVA under the control of human involucrin promoter (involucrin-mOVA mice). In contrast to previous strains, involucrin-mOVA mice spontaneously developed skin inflammation after the transfer of OT-I T cells in the absence of external stimuli without significant bodyweight loss. We focused on the skin infiltration process of OT-I T cells and found that transferred OT-I T cells accumulated around the hair follicles in the early phase of skin inflammation, and in the later phase, the skin inflammation spontaneously resolved despite the remaining OT-I T cells in the skin. Our involucrin-mOVA mice will provide a promising tool to investigate the pathogenesis and the tolerance mechanisms of cytotoxic skin autoimmunity.